2021
DOI: 10.1177/0011000021991877
|View full text |Cite
|
Sign up to set email alerts
|

Is Multicultural Counseling Competence Outdated or Underdeveloped, or in Need of Refinement? A Response to Ridley et al.

Abstract: This paper provides a response to Ridley et al.’s Major Contribution on the state of multicultural counseling competence (MCC) and their proposed refinement and extension of this construct. They pose the following multiprong question: “Is multicultural counseling competence becoming outdated and supplanted, or is it underdeveloped and in need of refinement?” We use this question to examine the MCC model that Ridley et al. have proposed in this Major Contribution. We summarize and critique each paper, and close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Training based on these MCC covered a variety of important identities of clients, with some identities receiving more attention than others. Originally, the focus on race and ethnicity was the priority of these multicultural counseling competencies (Vandiver et al 2021).…”
Section: Multicultural Counseling Competenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Training based on these MCC covered a variety of important identities of clients, with some identities receiving more attention than others. Originally, the focus on race and ethnicity was the priority of these multicultural counseling competencies (Vandiver et al 2021).…”
Section: Multicultural Counseling Competenciesmentioning
confidence: 99%
“…Although there is a clear push in the counseling field for considering the individual holistically in relation to the intersectionality of identities, the fear and challenge of bringing in spirituality and religion looms over counselors-in-training and those training them. This struggle is not surprising, given spirituality and religion were traditionally considered "taboo" in counseling and other mental health fields (Bergin 1980) and the focus of the MCC was originally on ethnicity and race (Sue et al 1982(Sue et al , 1992Vandiver et al 2021). Not all that long ago, almost 40% of surveyed counselors-in-training noted being taught directly or indirectly that they should not be addressing spirituality and religion in counseling (Adams 2012).…”
Section: Multicultural Counseling Competencies: Considering Spiritual...mentioning
confidence: 99%
See 1 more Smart Citation
“…I do not remember a time where we would start a client case conceptualization with the question, “How has systemic racism shaped the environment for this person, and how is it manifesting in this person’s current life?” Instead, these questions and concerns about race, racism, and experiences with inequities were often used to ameliorate a fairly traditional case conceptualization of the individual, regardless of their racial identities. I started to see that, potentially, multicultural competencies and cultural humility are theoretical adaptations—racialized psychological technologies—that work to adapt our traditional psychotherapy approaches and continue the relevance of these theoretical frameworks (Vandiver et al, 2021). These adaptive racialized technologies help produce generous revised renditions of traditional psychotherapy theories.…”
mentioning
confidence: 99%
“…difficult to learn compared to the other foundational counseling skills-and one's intent to learn alone does not guarantee competency will be achieved (e.g., Milan & Bridges, 2019;Vandiver et al, 2021). Within a racially heterogeneous sample, Zhang and McCoy (2008) found that although therapists endorse the value of multiculturally informed counseling interventions, such as bringing up racial differences with their clients, a smaller percentage of them actually follow through with these interventions.…”
mentioning
confidence: 99%